WATER CARRIER - KIRAN, K.RAVI; ARCHANA, B.; SATHISH, K.; AJAY, T.; HARSHITH, U. (The journal of contemporary issues in business and government, 2021)
The main aim of our project is to develop a mechanism for easy transportation of more water at a time from water pond, rivers, etc. , to their respective places. Water place a vital role in our daily life. Water is the major requirement in our day to day life, without water we can't do anything. Locally water will be carrying by women's from miles of distances to therehomes. Women's are used to carry the water on their head, while carrying the water on their heads, it causes the major effect on their spinal cord. To overcome this problem for women's we re- implemented this project for easy to carry of water. If they are tired ,While carrying of water they can take the rest under the metal sheet which is placed on the top of the carrier. It is also used to protect the carrier from the sun ray's. The main aim to develop this is, to help the women's who are carrying the water on their heads and to protect them from the injuries and causes from carrying of water on their heads.